Harmonization of Islamic Epistemology and Economics in Indonesia: A Study of the Islamization of Science Ismail Raji Al-Faruqi - Munir, Akhmad Sirojudin (Jurnal Multidisiplin Indonesia, 2024)
This research aims to explore efforts to harmonize Islamic epistemology and economics in Indonesia, with a special focus on the contribution of Ismail Raji Al-Faruqi's thoughts regarding the Islamization of Science. Al-Faruqi's thoughts on the integration of Islamic epistemology in economics are relevant in the current context, where economic issues are often handled without considering unique Islamic perspectives and values. This research uses a qualitative approach by conducting a literature review and content analysis of Ismail Raji Al-Faruqi's works that are relevant to the research theme. In addition, data will be collected from primary and secondary sources. Through in-depth analysis, this research will explore Al-Faruqi's views on the integration of Islamic epistemology and how these views can be adapted and implemented in the context of economic science in Indonesia. It is hoped that the results of this research will provide new insights into ways to accommodate Islamic values in economic theory and practice in Indonesia. This research can also provide a valuable contribution to the development of the study of the Islamization of Science and inspire further discussion and reflection regarding the harmonization between Islamic epistemology and contemporary science in various fields.